2010
DOI: 10.1586/eri.10.126
|View full text |Cite
|
Sign up to set email alerts
|

Early waning of maternal measles antibodies: why immunization programs should be adapted over time

Abstract: Primary protection against measles in the first months of life is provided by transferred maternal antibodies. Since the introduction of the measles vaccine, changes in epidemiology have had major effects on the transmission of protective antibodies. The majority of women of childbearing age are now vaccinated and transfer fewer antibodies than naturally immune mothers, conferring shorter protection to their offspring. This article reveals an early loss of maternal antibodies in infants of vaccinated mothers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, over the last decade, clusters of under-immunized individuals have led to community outbreaks by increasing transmission of VPD, 1 as observed with measles outbreaks in the USA, Canada, and Europe. [1][2][3][4] This phenomenon, called "vaccine hesitancy", is a growing issue that needs to be measured and addressed, according to the World Health Organization. 5 Vaccine hesitancy refers to delays in acceptance or refusal of vaccination despite the availability of vaccination services.…”
Section: Introductionmentioning
confidence: 99%
“…However, over the last decade, clusters of under-immunized individuals have led to community outbreaks by increasing transmission of VPD, 1 as observed with measles outbreaks in the USA, Canada, and Europe. [1][2][3][4] This phenomenon, called "vaccine hesitancy", is a growing issue that needs to be measured and addressed, according to the World Health Organization. 5 Vaccine hesitancy refers to delays in acceptance or refusal of vaccination despite the availability of vaccination services.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that the time of administering the first vaccine dose should be advanced. 15,16 However, other studies have reported that vaccination in younger infants (6-9 mo) usually results in lower seroconversion rates and neutralizing titers compared with immunization in older infants (12-15 mo). 17 In China, the first dose of measles vaccine is offered at 9 mo of age.…”
mentioning
confidence: 99%
“…Some researchers have suggested that the timing of the first vaccine dose should be advanced. 39,40 Aaby et al also found that child mortality may be reduced if measles vaccine is given earlier than currently recommended by international organizations. 41 With the presence of maternal antibody, child mortality in low-income countries may be reduced via a 2-dose vaccination schedule with the first dose at 4-6 months (earlier than currently recommended) and a booster dose at 9-12 months of age.…”
Section: Discussionmentioning
confidence: 99%